Application of High-Throughput Flow Cytometry in Early Drug Discovery: An AstraZeneca Perspective. (August 2018) - Ding, Mei; Clark, Roger; Bardelle, Catherine; Backmark, Anna; Norris, Tyrrell; Williams, Wendy; Wigglesworth, Mark; Howes, Rob
Flow cytometry is a powerful tool providing multiparametric analysis of single cells or particles. The introduction of faster plate-based sampling technologies on flow cytometers has transformed the technology into one that has become attractive for higher throughput drug discovery screening. This article describes AstraZeneca's perspectives on the deployment and application of high-throughput flow cytometry (HTFC) platforms for small-molecule high-throughput screening (HTS), structure–activity relationship (SAR) and phenotypic screening, and antibody screening. We describe the overarching HTFC workflow, including the associated automation and data analysis, along with a high-level overview of our HTFC assay portfolio. We go on to discuss the practical challenges encountered and solutions adopted in the course of our deployment of HTFC, as well as future enhancements and expansion of the technology to new areas of drug discovery.